2004
DOI: 10.1099/ijs.0.02814-0
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiopsis aegyptia sp. nov., isolated from marine sediment

Abstract: An actinomycete, strain SNG49 T , was isolated from marine sediment of Abu Qir Bay, on the western seashore of Alexandria, Egypt. The bacterium was aerobic and Gram-positive. It produced beige to light-yellow aerial mycelium, brown substrate mycelium and straight to flexuous hyphae, but no specific spore chains. 16S rDNA sequence analysis and chemotaxonomic markers were consistent with classification of strain SNG49T in the genus Nocardiopsis, i.e. mesodiaminopimelic acid; no diagnostic sugars; phosphatidylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 21 publications
(23 reference statements)
1
36
1
Order By: Relevance
“…T was proposed and the phylogenetic analysis was carried out (Sabry et al, 2004 Polymeric materials. Poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxy-butyrate-co-3-hydroxyvalerate) P(3HB-co-10-20% HV) were obtained as powders from Aldrich (Steinheim, Germany) and ICI (Brillingham, UK), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…T was proposed and the phylogenetic analysis was carried out (Sabry et al, 2004 Polymeric materials. Poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxy-butyrate-co-3-hydroxyvalerate) P(3HB-co-10-20% HV) were obtained as powders from Aldrich (Steinheim, Germany) and ICI (Brillingham, UK), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of writing, the taxon encompasses 24 recognized species (Li et al, 2006), which form a distinct clade within the evolutionary radiation occupied by members of the family Nocardiopsaceae (Rainey et al, 1996;Cui et al, 2001;Kroppenstedt & Evtushenko, 2006). Nocardiopsis strains are frequently isolated from saline and alkaline soils (Li et al, , 2006Hozzein et al, 2004), but have also been recovered from an alkaline slag dump (Schippers et al, 2002), clinical material (Yassin et al, 1997;Mordarska et al, 1998), indoor environments (Peltola et al, 2001), the atmosphere of a composting facility (Kämpfer et al, 2002) and a marine sediment (Sabry et al, 2004). In the present polyphasic study, an actinomycete isolated from a sand-dune soil was shown to represent a novel species of the genus Nocardiopsis.…”
mentioning
confidence: 99%
“…Most strains of the genus Nocardiopsis were isolated from hypersaline soils (M.-G. W.-J. Li et al, , 2006Chen et al, 2008;Yang et al, 2008) and some strains were isolated from marine sediments (Sabry et al, 2004;Kroppenstedt & Evtushenko, 2006;Tian et al, 2009). The four species of the genus Thermobifida were isolated from composts or damp stored hay (Zhang et al, 1998), manure heaps (Kukolya et al, 2002) and a salt mine .…”
mentioning
confidence: 99%